Impurity and purification in early Judaism and the Jesus tradition - Kazen, Thomas (Resources for biblical study, 2021)
"This collection of twelve essays by Thomas Kazen focuses on issues of purity and purification in early Judaism and the Jesus tradition. During the late Second Temple period, Jewish purity practices became more prominent than before and underwent substantial developments. Kazen advances the ongoing conversation and debate about a number of key issues in the field, such as the relationship between ritual and morality, the role and function of metaphor, and the use of evolutionary and embodied perspectives"--